Effects of feeding β-carotene on levels of β-carotene and vitamin A in blood and tissues of beef cattle and the effects on beef quality. (December 2015) - Jin, Qing; Cheng, Haijian; Wan, Fachun; Bi, Yulin; Liu, Guifen; Liu, Xiaomu; Zhao, Hongbo; You, Wei; Liu, Yifan; Tan, Xiuwen
Abstract: The effects of feeding β-carotene (βC) on levels of βC and vitamin A (retinol) in blood and tissues, and on beef quality, were evaluated in 120 steers. Each steer received supplementary βC (at concentrations of 0, 600, 1200, or 1800 mg/day) for 90 days and then received no supplementary βC for 60 days. βC significantly increased in blood serum, liver, and subcutaneous and omental fat; linearly increased in the intestine and muscle; and remained unchanged in perirenal fat during supplementation. Differences between treatment groups were eliminated in subcutaneous and omental fat and in the liver by days 120 and 150, respectively, but remained significant at day 150 in blood. Retinol increased significantly in the liver and intestine during supplementation. Intramuscular fat content, meat color, and retinol in blood, muscle, or adipose tissues were not affected. Backfat thickness decreased slightly with increasing βC supplementation and significantly differed between groups during depletion.